Assessing the Robustness of Pan Evaporation Models for Estimating Reference Crop Evapotranspiration during Recalibration at Local Conditions (2021)
Babakos, K., D. Papamichail, P. Tziachris, V. Pisinaras, K. Demertzi, and V. Aschonitis. 2020. Assessing the Robustness of Pan Evaporation Models for Estimating Reference Crop Evapotranspiration during Recalibration at Local Conditions. Hydrology 7, 62. https://doi.org/10.3390/hydrology7030062